Use and application of information mapping as teaching resources for teaching RDA in Special Information Resource Organization courses - Ruiz Bustos, Ana Priscilla (2026)
The Library Science and Information Management program at the National University of Costa Rica includes in its curriculum the course Organization of Special Information Resources, which focuses on the technical description of non-conventional materials under international standards (RDA) (Resources, Description, and Access). Mastering this conceptual and procedural knowledge requires innovative teaching strategies that go beyond traditional teaching methods. In this context, this research analyzes the relevance of information mapping as a didactic and methodological approach to facilitate the identification of attributes and elements in special resources. The main objective is to analyze the impact of the application of information mapping as a teaching-learning strategy on students who took the Special Information Resources Organization course during the years 2023-2024 for the understanding of conceptual and procedural knowledge. Methodologically, the study is descriptive in nature with a quantitative approach, applied to a sample of third- and fourth-year students. For data collection, a structured questionnaire with 19 multiple-choice questions was used via the Google Forms platform. The results show that the implementation of information mapping as a pedagogical strategy enhances meaningful learning and strengthens the technical understanding of the student population in the area of document organization.